Hyperacute Rejection of a Living Unrelated Kidney Graft. (16th September 2014) - Tittelbach-Helmrich, Dietlind; Bausch, Dirk; Drognitz, Oliver; Goebel, Heike; Schulz-Huotari, Christian; Kramer-Zucker, Albrecht; Hopt, Ulrich Theodor; Pisarski, Przemyslaw
Abstract : We present a case report of a 59-year-old man, who received a blood group identical living unrelated kidney graft. This was his second kidney transplantation. Pretransplant T-cell crossmatch resulted negative. B-cell crossmatch, which is not considered a strict contraindication for transplantation, resulted positive. During surgery no abnormalities occurred. Four hours after the transplantation diuresis suddenly decreased. In an immediately performed relaparotomy the transplanted kidney showed signs of hyperacute rejection and had to be removed. Pathological examination was consistent with hyperacute rejection. Depositions of IgM or IgG antibodies were not present in pathologic evaluation of the rejected kidney, suggesting that no irregular endothelial specific antibodies had been involved in the rejection. We recommend examining more closely recipients of second allografts, considering not only a positive T-cell crossmatch but also a positive B-cell crossmatch as exclusion criteria for transplantation.